PENGARUH PROFITABILITAS, DEBT DEFAULT DAN AUDIT TENURE TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Selvy Lintang Tamida; Harry Budiantoro; Kanaya Lapae (Jurnal Riset Akuntansi, 2022)
With firm size acting as a moderating variable, the purpose of this study was to determine the effect of profitability, debt default, and audit tenure, going concern audit opinion. Trading, service, and investment companies listed on the Indonesia Stock Exchange for 2017 - 2021 are the samples used in this study. 61 companies were selected as part of the purposive sampling technique used in this study. This study uses secondary data, particularly the company's financial statements collected from the official website of the Indonesia Stock Exchange (IDX). Logistic regression with SPSS version 26 was used as the analytical technique. According to research findings, profitability and debt default affect going concern audit opinion. Going concern audit opinion is not affected by the audit period. Profitability and debt default on going concern opinion can be moderated by company size, but not able to moderate the audit period.